A High‐Performance Self‐Powered Photodetector Based on MAPbBr3 Single Crystal Thin Film/MoS2 Vertical Van Der Waals Heterostructure. Issue 27 (15th August 2022) - Xu, Zhongquan; Zeng, Yonghong; Meng, Fanxu; Gao, Shan; Fan, Sidi; Liu, Yi; Zhang, Yule; Wageh, Swelm; Al‐Ghamdi, Ahmed A.; Xiao, Jing; Guo, Zhinan; Zhang, Han
Abstract: Methylammonium lead bromide (MAPbBr3 ) single crystal thin film shows great opportunities in high‐performance optoelectronic devices due to its high absorption coefficient, high photoelectric conversion efficiency, and low trap‐state density properties. In order to fabricate a highly sensitive self‐powered photodetectors, herein, a MAPbBr3 single crystal thin film/molybdenum disulfide (MoS2 ) vertical p‐n heterostructure based photodetector has been built by typical polymer film assisted dry transfer method and micromachining technique. Attributing to the built‐in electric field and the shortened transmit distance for the photogenerated carriers in this heterostructure, the device shows excellent photovoltaic characteristics with a maximum output electrical power of 7 nW and power conversion efficiency of 8% at 0.34 V under 532 nm laser. Moreover, prominent photoelectric properties with responsivity of 368 mA W −1 and detectivity of 3.74 × 10 12 Jones for 532 nm laser without any bias have been achieved, which are ranking high among the organic–inorganic hybrid perovskites based self‐power photodetectors. These results demonstrate that the MAPbBr3 single crystal thin film/MoS2 vertical heterostructure can pave a new way to develop high‐performance photovoltaic devices. Abstract : A methylammonium lead bromide single crystal thin film/molybdenum disulfide (MoS2 ) vertical p‐n heterostructure based photodetector has been built, which shows excellent photovoltaic characteristics with power conversion efficiency of 8% and prominent photoelectric properties with responsivity of 368 mA W −1 under 532 nm laser, resulting from the built‐in electric field and the shortened transmit distance for the photogenerated carriers in this heterostructure.